Trust as the Gateway to Islamic Bank Adoption: Integrating Digital Religious Influence and Management Capability - Kurniawati Mulyanti; Sri Rusiyati; Tuti Sulastri; Jamalludin Harahab (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine customer adoption of Bank Syariah Indonesia (BSI) by applying a parsimonious Stimulus–Organism–Response (SOR) framework that integrates digital religious influence and institutional capability to explain adoption decisions in the context of Islamic banking. Methodology: The study employed a quantitative survey approach using mixed-mode data collection (online and on-site questionnaires). Data were collected from 325 active BSI customers located in the Jakarta–Bogor–Depok–Tangerang–Bekasi (Jabodetabek) area. Online Religious Leaders and Managerial Performance were modeled as exogenous stimuli, Product Value Trust as the organismic variable, and the Decision to Become a BSI Customer as the response variable. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results: The findings indicate that Online Religious Leaders and Managerial Performance significantly enhance Product Value Trust, which in turn positively influences customers’ adoption decisions. Both stimuli also exhibit significant direct effects on adoption decisions. Mediation analysis confirms that Product Value Trust partially mediates the relationship between the stimuli and customer adoption. Conclusions: The results demonstrate that customer adoption of Islamic banking is shaped by the alignment of credible religious influence and visible managerial performance that collectively strengthen trust in product value. Limitations: This study is limited to customers in the Jabodetabek area and relies on cross-sectional data. Contributions: This study contributes to Islamic banking and consumer behavior literature by identifying Product Value Trust as a central mechanism linking digital religious influence and institutional capability to customer adoption decisions.